Features of the respiratory and cardiovascular system responses of girls 10-12 years of age on the swimming load - Natalia Balamutova; Grigory Kucherenko; Svetlana Shiryaeva; Liliya Sheyko (Kharkiv State Academy of Physical Culture, 2019)
Purpose: study of the respiratory and cardiovascular system responses of girls aged 10-12 years on a dosed swimming load. Material & Methods: the study involved 45 girls of 10-12 years old, engaged in the section of sports swimming. The method of spirography was measured: BH, RV, Рv of inhalation and exhalation, VC, МBV, МVL, RB, OC2. Cardiovascular parameters were recorded: HR, BP, SV, МBV. Results: the study showed that swimming the control 50 and 100-meter distances in the same age group is different due to the effect on the respiratory and circulatory systems, depending on the sport of swimming. Conclusion: the results of the study showed that the greatest impact on the indices of the cardiorespiratory system of adolescents aged 10-11 years was observed while swimming the back crawl; and 12-year-old subjects performed larger loads "more economically". The dynamics of the studied functional systems of 12-year-olds showed that the greatest changes are observed when swimming 100 m breaststroke. In general, the load of 50 and 100 m distances is feasible for teenagers with all the sports swimming methods being studied.